PENGARUH ESG DISCLOSURE DAN KUALITAS LAPORAN KEUANGAN TERHADAP EFISIENSI INVESTASI - Nurul Fadiyah Nasution; Wahyu Meiranto (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of ESG disclosure and financial reporting quality on investment efficiency in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2021-2023.            This study uses a quantitative approach with secondary data obtained from Bloomberg Terminal and company annual reports. The research sample was determined using purposive sampling, resulting in 65 observation samples. The analysis method used was multiple linear regression.            The results show that ESG disclosure and financial reporting quality do not significantly affect investment efficiency. These findings indicate that sustainability information and financial reporting quality are not yet major factors in determining the level of investment efficiency of companies during the research period.